2007
DOI: 10.1017/s0031182007003307
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of actin genes inBonamia ostreaeand their application to phylogeny of the Haplosporidia

Abstract: Bonamia ostreae is a protozoan parasite that infects the European flat oyster Ostrea edulis, causing systemic infections and resulting in massive mortalities in populations of this valuable bivalve species. In this work, we have characterized B. ostreae actin genes and used their sequences for a phylogenetic analysis. Design of different primer sets was necessary to amplify the central coding region of actin genes of B. ostreae. Characterization of the sequences and their amplification in different samples dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Moreover, the DNA sequence analysis supported, in 2 samples, the occurrence of microcells belonging to B. exitiosa, thus corroborating the recent report of this species in European flat oysters (Abollo et al 2008). B. exitiosa is known to infect O. chilensis in New Zealand (Dinamani et al 1987) and O. angasi in Australia (Hine & Jones 1994, Hine 1996, Corbeil et al 2006, while other parasites, referred to as B. exitiosa (Lopez-Flores et al 2007), have been reported in O. chilensis in Chile (Campalans et al 2000), in O. puelchana in Argentina (Kroeck & Montes 2005), and in Crassostrea ariakensis in North Carolina, USA ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the DNA sequence analysis supported, in 2 samples, the occurrence of microcells belonging to B. exitiosa, thus corroborating the recent report of this species in European flat oysters (Abollo et al 2008). B. exitiosa is known to infect O. chilensis in New Zealand (Dinamani et al 1987) and O. angasi in Australia (Hine & Jones 1994, Hine 1996, Corbeil et al 2006, while other parasites, referred to as B. exitiosa (Lopez-Flores et al 2007), have been reported in O. chilensis in Chile (Campalans et al 2000), in O. puelchana in Argentina (Kroeck & Montes 2005), and in Crassostrea ariakensis in North Carolina, USA ).…”
Section: Discussionmentioning
confidence: 99%
“…B. perspora is a newly described protozoan species found in Ostreola equestris (North Carolina, USA) and represents the first Bonamia species producing a typical haplosporidian spore (Carnegie et al 2006). Other B. exitiosa-like organisms have been described in O. chilensis from Chile (Kern 1993, Campalans et al 2000, O. puelchana from Argentina (Kroeck & Montes 2005), and Crassostrea ariakensis from North Carolina ); these organisms have been subsequently declared B. exitiosa (Lopez-Flores et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…and Minchinia spp. The relationship with the latter and H. costale has recently been supported in phylogenies based on actin gene sequences (López-Flores et al 2007), and on a prawn haplosporidian (Nunan et al 2007). Future studies may confirm the placing of crustacean haplosporidians close to or between Bonamia spp.…”
Section: Haplosporogenesismentioning
confidence: 71%
“…are parasites of bivalve hosts, and currently 4 species are recognised in the genus, namely B. ostreae, B. exitiosa, B. perspora and B. roughleyi (Pichot et al 1980, Cochennec-Laureau et al 2003, Reece et al 2004, Carnegie et al 2006, López-Flores et al 2007. With the exception of B. perspora, these normally occur within haemocytes of the host (Cochennec-Laureau et al 2003); B. perspora occurs within connective tissues of its host Ostreola equestris (Carnegie et al 2006).…”
Section: Introductionmentioning
confidence: 99%